Nucleic acid amplification strategies for volume-amplified magnetic nanoparticle detection assay - Huang, Zhongchao; Li, Jing; Zhong, Hongwen; Tian, Bo (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic nanoparticles (MNPs) can be quantified based on their magnetic relaxation properties by volumetric magnetic biosensing strategies, e.g., alternating current susceptometry. Volume-amplified magnetic nanoparticle detection assays (VAMNDAs) employ analyte-initiated nucleic acid amplification (NAA) reactions to increase the hydrodynamic size of MNP labels for magnetic sensing, achieving attomolar to picomolar detection limits. VAMNDAs offer rapid and user-friendly analysis of nucleic acid targets, but present inherence defects determined by the chosen amplification reactions and sensing principles. In this mini-review, we summarize more than 30 VAMNDA publications and classify their detection models for NAA-induced MNP size increases, highlighting the performances of different linear, cascade, and exponential NAA strategies. For some NAA strategies that have not yet been reported in VAMNDA, we predicted their performances based on the reaction kinetics and feasible detection models. Finally, challenges and perspectives are given, which may hopefully inspire and guide future VAMNDA studies.